Tantangan dalam Perawatan Oral Lichen Planus pada Pasien Diabetes Melitus (Laporan Kasus) - Ravina Naomi Tarigan; Titiek Setyawati (Faculty of Dentistry, Universitas Indonesia, 2012)
Oral lichen planus (OLP) is a chronic inflammatory condition that effects oral mucous membranes with a variety of clinical presentations including reticular, atrophic, plaque and ulcerative lesions. Corticosteroid is one of the effective therapy for OLP in reducing the sign and symptoms of this disease, but this therapy have a serious side effect, therefore to administering one must consider the patient's systemic condition. We reported a case of OLP in 52 years old female patient who has no history of diabetes mellitus and unknown glucose level. Management of this patient included application of corticosteroid swish, topical 0.05% clobetasol propionate and 0,1% triamcinolone acetonide, antimycotics, improvement the oral hygiene status and referral to internal medicine specialist. The next treatments plan challenging because unstable blood glucose level which in turn effects the drug choice and teeth extraction plan. We concluded that the treatment of OLP requires a complete assessment of medical status and lab studies specially on the first visit so the drug selection with corticosteroid therapy and the treatment planning of predisposing factor are effective in reducing the sign and symptoms of OLP with minimum systemic side effect. DOI: 10.14693/jdi.v16i1.19